Ubezpieczenia oszczędnościowe a funkcja ochronna ubezpieczeń na życie w Polsce w latach 2001-2006 - Kania, Piotr; Szewieczek, Daniel (Savings-Life Insurance and the Protection Function of Life Insurance, 2008)
There is a strong correlation between saving and protection function in the life insurance contract. Traditional life insurance is used to provide a certain sum on death of an individual but this protection is very often combined with a savings option. In saving-life insurance the saving-premium is directly allocated to the separated funds or can be recorded on individual account and invested together with company's assets. There are changes observed in the Polish insurance market connected with the need for protection and investments. New products offered by life insurance companies provide more opportunities to collect savings and invest but at the same time the financial consequences of the death are low covered. Due to low protection component the insurance premium is low charged by the risk allowances. Additionally the savings-policies are supported by a tax incentive which makes them more attractive.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 147-156